Reports on Ongoing and Past Research Project Laboratorium Bantenologi’s Biographies of Ulama and Religious Leaders in Banten 1810-2000 - Mufti Ali; Ade Jaya Suryani (Kawalu: Journal of Local Culture, 2015)
Reports on Ongoing and Past Research Project Laboratorium Bantenologi’s Biographies of Ulama and Religious Leaders in Banten 1810-2000